A Phase II Trial of Onapristone and Fulvestrant for Patients With ER+ and HER2- Metastatic Breast Cancer - Kamaraju, Sailaja; Fowler, Amy M.; Tarima, Sergey; Chaudhary, Lubna N.; Burkard, Mark E.; Giever, Thomas; Cheng, Yee C.; Parkes, Amanda; Lange, Carol A.; Pipp-Dahm, Michele; Hegeman, Robert; Siddiqui, Nauman; et al. (Clinical breast cancer, 2025)
The SMILE study is a multi-institutional phase II clinical trial to determine the efficacy and safety of an antiprogestin, onapristone, in combination with fulvestrant as second-line therapy for patients with ER+, PgR+/-, HER2- metastatic breast cancer. This study was terminated early and herein, we report patient characteristics, and outcomes. Eligibility criteria included disease progression on ≥2 lines of prior therapy, ECOG performance status ≤ 2, measurable disease per RECIST 1.1 criteria, and optional 18F-fluorofuranylnorprogesterone (18F-FFNP) PET/CT imaging. Consented subjects received standard-dose fulvestrant plus onapristone 50 mg orally, twice daily, until disease progression, or unacceptable toxicity. The study enrolled 11 women from 2 sites within the Wisconsin Oncology Network from November 2021 through March 2023. Mean age of the subjects was 58.5 years. Other than grade 1 toxicities, the treatment was well tolerated. None of the 11 subjects met RECIST 1.1 definition of response. The median time to progression was 63 days. A total of 4 of 11 patients had stable disease as best response and 2 of them were on treatment for 5.5 and 7.7 months. Two of the 11 subjects underwent functional imaging with 18F-FFNP PET/CT before and 10 or 14 days after starting treatment. For both subjects, tumor uptake of 18F-FFNP was stable or increased in all target lesions while 18F-FFNP uptake in the uterus, a normal PgR-rich internal control organ, was decreased. The study regimen was well-tolerated with no significant toxicities. Future studies may evaluate antiprogestins with various combinations such as targeted therapies. The SMILE study, a phase II clinical trial of onapristone plus fulvestrant in ER+, PgR+/−, HER2− metastatic breast cancer, enrolled 11 women but was terminated early. Despite good tolerability and grade 1 toxicities, no RECIST 1.1 responses were observed, with a median time to progression of 63 days. Stable disease was achieved in 4 patients, with two remaining on treatment for >5 months. 18F-FFNP PET/CT imaging revealed stable or increased tumor uptake, suggesting potential for future studies combining antiprogestins with targeted therapies.